State and sustainable development in Brazil: Water, biomass and oil (1992 - 2012) - Peguim, Cássia Natanie [UNESP] (My University, 2017)
In this article we examined the economical options adopted by the Brazilian State in the use of the water, biomass and petroleum for the generation of energy in the period 1992 to 2012 observing the existence of the demand for politics promoters of maintainable development. In the decade of 1990 the neoliberal politics took to the privatizations in a moment of pressure for the resourves natural generators of energy at the same time in that Brazil visibility in the discussion on energy sources no pollutant, as the hydroelectric power station and generatedby biomass. That path is interrupt with the discovery and exploration of the Pré-Salt, a fossil source of energy. In the period, the concern with the safety energy runs through the action of the State.
Estado e Desenvolvimento Sustentável no Brasil: Água, Biomassa e Petróleo (1992 - 2012)
Keywords: Brazil; Natural Resources; State; Sustainable Development